Liver disease related to alpha1‐antitrypsin deficiency in French children: The DEFI‐ALPHA cohort. (1st February 2019) - Ruiz, Mathias; Lacaille, Florence; Berthiller, Julien; Joly, Philippe; Dumortier, Jérôme; Aumar, Madeleine; Bridoux‐Henno, Laure; Jacquemin, Emmanuel; Lamireau, Thierry; Broué, Pierre; Rivet, Christine; Belmalih, Abdelouahed; et al.
Abstract: Background & Aims: To identify prognostic factors for liver disease in children with alpha‐1 antitrypsin deficiency, irrespective of phenotype, using the DEFI‐ALPHA cohort. Methods: Retrospective, then prospective from 2010, multicentre study including children known to have alpha‐1 antitrypsin blood concentration below 0.8 g/L, born in France since 1989. Clinical and biological data were collected. Liver disease was classified as "severe" (portal hypertension, liver failure, liver transplantation or death); "moderate" (persistent abnormal liver biology without portal hypertension); and "mild/none" (normal or almost normal liver biology and native liver). Prognostic factors for severe liver disease were evaluated using a Cox semiparametric model. Results: In January 2017, 153 patients from 19 centres had been included; genotypes were PIZZ in 81.9%, PISZ in 8.1%, other in 10.0%. Mean ± SD follow‐up was 4.7 ± 2.1 years. Half of patients had moderate liver disease. Twenty‐eight children (18.3%) had severe liver disease (mean age 2.5 years, range: 0‐11.6): diagnosis of alpha‐1 antitrypsin deficiency was made before two months of age in 65.4%, genotypes were PIZZ in 25 (89.3%), PISZ in 2, PIMlike Z in 1, 15 children underwent liver transplantation, 1 child died at 3 years of age. Neonatal cholestasis was significantly associated with severe liver disease ( P = 0.007). Conclusion: Alpha‐1 antitrypsin‐deficient patients presenting with neonatal cholestasis were likely to develop severe liver disease. Some patients with non‐homozygous ZZ genotype can develop severe liver disease, such as PISZ and M variants, when associated with predisposing factors. Further genetic studies will help to identify other factors involved in the development of liver complications. Abstract : See Editorial on Page1019